Letrozole Versus Clomiphene Citrate and Natural Cycle: Endometrial Receptivity During Implantation Window in Women With Polycystic Ovary Syndrome - Wang, Li; Lv, Shulan; Li, Fen; Bai, E.; Yang, Xiaofeng (Frontiers in Endocrinology, 2021)
Objective Numerous studies have reported on ovulation and pregnancy rates in patients with polycystic ovary syndrome (PCOS). However, relevant data on endometrial receptivity are limited. This study was conducted to compare endometrial receptivity during implantation windows among letrozole (LE), clomiphene citrate (CC), and natural cycle, and to assess the predictive value for pregnancy of observed indicators. Methods This randomized controlled trial study enrolled 270 patients with PCOS. Patients were given LE (n=90) at a dose of 2.5mg/day or CC (n=90) at a dose of 50 mg/day on cycle days 5–9 for ovulation induction. Patients in the natural cycle group (n=90) did not receive any drug for ovulation induction. Endometrial ultrasonic parameters, integrin αvβ3, and vascular endothelial growth factor (VEGF) concentrations in uterine secretion were detected during the implantation window. The endometrial receptivity, ovulation rate, pregnancy rates, and predictive value of observed indicators for pregnancy were analyzed. Results The successful ovulation rate did not differ between the LE group and CC group (P>0.05). Endometrial ultrasonic parameters [endometrial thickness (ET), endometrial volume (EV), vascularization index (VI), flow index (FI), vascularization flow index (VFI)], integrin αvβ3, and VEGF concentrations in uterine fluid were significantly higher in the LE group compared with the CC group and natural cycle group (P<0.05). The clinical pregnancy and ongoing pregnancy rates of the LE group were significantly higher than in the CC group (P<0.05). Endometrial ultrasonic parameters (VI, FI, and VFI), integrin αvβ3, and VEGF concentrations in uterine fluid of all pregnancy groups were significantly higher compared with the no pregnancy group (P<0.05), and the above parameters in ongoing pregnancy were significantly higher than in biochemical pregnancy (P<0.05). The endometrial FI during the implantation window had the highest predictive value for pregnancy (AUC=0.889). The integrin αvβ3 in uterine fluid had better predictive value (AUC=0.876) than VEGF. Conclusions Endometrial receptivity during the implantation window of LE is superior to CC in PCOS women, which may be related to higher clinical pregnancy and ongoing pregnancy rates. Endometrial FI examined by 3-D power Doppler, and integrin αvβ3 in uterine secretion during the implantation window, could be preferable non-invasive predictor markers for pregnancy. Clinical Trial Registration www.chictr.org.cn, ChiCTR1900023423.